Detoxification of the mycoestrogen zearalenone by Bacillus licheniformis spore CotA laccase and application of immobilized laccase in contaminated corn meal. (15th June 2022) - Guo, Yongpeng; Wang, Yanan; Liu, Yanrong; Ma, Qiugang; Ji, Cheng; Zhao, Lihong
Abstract: Zearalenone (ZEN) is an estrogen-like mycotoxin posing a great threat to human and animal health. The present study showed that the induction of spore CotA laccase production of Bacillus licheniformis by ions Mn 2+ and Cu 2+ promoted the ZEN-degrading ability of the strain. The spore CotA laccase heterologously expressed in Escherichia coli was capable of directly oxidizing ZEN with K m, K cat and Vmax values of 90.43 μg mL −1, 0.11s −1 and 35.48 μg min −1 mg −1, respectively. The use of 2, 2′-azino-bis-(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS), acetosyringone, ferulic acid, caffeic acid and methyl syringate as redox mediators could enhance ZEN degradation by CotA laccase. The human breast cancer MCF-7 cell proliferation assay showed that CotA laccase and CotA laccase-mediator systems eliminated the estrogenicity of ZEN. Immobilized CotA laccase onto chitosan microspheres exhibited higher thermal stability over free CotA laccase, maintaining about 87% of its initial activity after heat treatment at 80 °C for 30 min. The removal rate of ZEN in corn meal by free and immobilized CotA laccase was 70% and 90%, respectively. Meanwhile, immobilized enzyme could achieve a 54% ZEN degradation in corn meal after three consecutive cycles. Thus, CotA laccase could be a promising biocatalyst for detoxification of ZEN in corn meal. Highlights: CotA laccase was capable of directly oxidizing ZEN. Redox mediators could enhance the ZEN-degrading ability of CotA laccase. CotA laccase-catalyzed ZEN degradation mitigated its estrogenicity. Immobilized CotA laccase displayed higher thermal stability than free CotA laccase. Immobilized CotA laccase could degrade 90% of ZEN in corn meal.